Nuevos sistemas electroquímicos y fotoquímicos para el tratamiento de aguas residuales y de bebida (2005)
ABSTRACT: With the increasing pressure on a more effective use of water resources, the developpement of appropriate water treatment technologies become more and more important. Photochemical and electrochemical oxidation processes have been proposed in recent years as an attractive alternative for the treatment of contaminated water containing anthropogenic substances hardly biodegradable as well as to purify and disinfect drinking waters. The aim of this paper is to present some of our last results demonstrating that electrochemical, photochemical, and the coupling of these processes with biological systems are very promising alternatives for the improvement of the water quality.